Proceedings of the 2015 ACM Conference on Innovation and Technology in Computer Science Education 2015
DOI: 10.1145/2729094.2742611
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Factors Influencing Pursuit of Computer Science and Related Fields

Abstract: Increasing women's participation in computer science is a critical workforce and equity concern. The technology industry has committed to reversing negative trends for women in computer science as well as engineering and information technology "computing" fields. Building on previously published research, this paper identifies factors that influence young women's decisions to pursue computer science-related degrees and the ways in which these factors differ for young men. It is based on a survey of 1,739 high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 16 publications
(12 reference statements)
3
60
1
9
Order By: Relevance
“…A recent Google report emphasised the need for parents, students and educators to be made more aware of the benefits of CS education [26]. Numerous studies have identified the significance of social support as an influence on females to choose to study CS [19,57,61,63]. Mishkin et al [43] found that female students making an engineering career choice are influenced by social support more than male students.…”
Section: Social Supportmentioning
confidence: 99%
“…A recent Google report emphasised the need for parents, students and educators to be made more aware of the benefits of CS education [26]. Numerous studies have identified the significance of social support as an influence on females to choose to study CS [19,57,61,63]. Mishkin et al [43] found that female students making an engineering career choice are influenced by social support more than male students.…”
Section: Social Supportmentioning
confidence: 99%
“…But while the number of women who major in STEM disciplines is trending upwards, the number of women earning degrees in technologyrelated disciplines is not. For example, while women earned about 58 percent of the STEM-related degrees in 2014, they earned only about 18 percent of the degrees awarded in computer and information sciences in 2014-down from a peak of 37 percent in the mid-1980s (National Center for Education Statistics, 2015;Sax et al, 2017;Wang, Hong, Ravitz, & Ivory, 2015).…”
Section: Figure 1 Percent Of Female Employees At Selected Technologymentioning
confidence: 99%
“…Over the last two decades, many studies have queried women about their interest in technology-related disciplines using surveys, focus groups, and direct interviews (Beyer, 2008(Beyer, , 2014Buschor, Berweger, Frei, & Kappler, 2014;Cory, Parzinger, & Reeves, 2006;Geyfman, Force, & Davis, 2016;Joshi & Schmidt, 2006;Merhout, Havelka, & Rajkumar, 2016;Stout, Grunberg, & Ito, 2016;Wang et al, 2015;Zhang, 2007). These studies have found that parental influence, role models, stereotypes, knowledge of the field, influence of peers, self-efficacy, and external encouragement are important factors that affect women's interest in IS.…”
Section: Figure 1 Percent Of Female Employees At Selected Technologymentioning
confidence: 99%
“…In order to attract more females to the IT profession, there is a need to focus on how to make the study of IT attractive to secondary school students (Wang, Hong, Ravitz, & Ivory, 2015;Yansen, 2014;Zagami et al, 2015). The situation is complex to remedy (Ridley & Young, 2012) and requires intervention to influence perceptions of careers in the IT workforce (Quesenberry & Trauth, 2012).…”
Section: Gender Diversity In Itmentioning
confidence: 99%